Traditional herbal medicine: Therapeutic potential in rheumatoid arthritis. (28th October 2021) - Wang, Yuan; Chen, Shujing; Du, Kunze; Liang, Chunxiao; Wang, Shuangqi; Owusu Boadi, Evans; Li, Jin; Pang, Xiaoli; He, Jun; Chang, Yan-xu
Abstract: Ethnopharmacological relevance: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease influenced by diverse endogenous and exogenous factors. It is characterized by cartilage and bone destruction. The current conventional allopathic therapy is expensive and carries adverse side effects. Recently, there were some ethnopharmacological studies on RA including anti-RA effects and therapeutic targets of distinct dosage forms of traditional herbal medicines (THMs). Aim of the review: This review provides a brief overview of the current understanding of the potential pharmacological mechanisms of THMs (active constituents, extracts and prescriptions) in RA. This study is intended to provide comprehensive information and reference for exploring new therapeutic strategies of THMs in the RA treatment. Materials and methods: This review captured scientific literatures in vivo and vitro experiments on effects of anti-RA THMs published between 2016 and 2021 from journals and electronic databases (e.g. PubMed, Elsevier, Science Direct, Web of Science and Google Scholar). Relevant literatures were searched and analyzed by using keywords such as 'rheumatoid arthritis AND traditional herbal medicines', 'rheumatoid arthritis AND immune cells', 'rheumatoid arthritis AND inflammation', 'rheumatoid arthritis AND miRNA', 'rheumatoid arthritis AND Angiogenesis', 'rheumatoid arthritis AND oxidative stress', 'rheumatoid arthritis AND osteoclasts', 'rheumatoid arthritis AND CIA model', 'rheumatoid arthritis AND AA model' AND 'rheumatoid arthritis herbal prescription'. Results: Experiments in vitro and in vivo jointly demonstrated the potential of THMs in the RA treatment. There are plentiful therapeutic targets in RA. THMs and active ingredients could alleviate RA symptoms through different therapeutic targets, such as immunoregulation, inflammation, fibroblast-like synoviocytes (FLSs), microRNAs (miRNAs), angiogenesis, oxidative stress, osteoclasts and multiple targets interaction. Anti-RA THMs, active ingredients and prescriptions through corresponding therapeutic targets were summarized and classified. Conclusions: Flavonoids, phenolic acids, alkaloids and triterpenes of THMs are identified as the main components to ameliorate RA. Regulation of different and multiple related therapeutic targets by THMs and their active ingredients were associated with greater therapeutic benefits, among which inflammation is the main therapeutic target. Nonetheless, further studies are required to unravel the complexities and in-depth mechanisms of THMs in alleviating RA. Graphical abstract: Image 1 Highlights: THM for the treatment of Rheumatoid arthritis. The active ingredients of THM display strong anti-RA effects. THM may has multiple targets for RA treatment. Flavonoids may exerted major anti-RA effects in THM. Anti-inflammatory mechanism is the main anti-RA target of THM.